2019
DOI: 10.17269/s41997-018-0168-9
|View full text |Cite
|
Sign up to set email alerts
|

Municipal transportation policy as a population health intervention: estimating the impact of the City of Ottawa Transportation Master Plan on diabetes incidence

Abstract: Intervention Physical inactivity is an important behavioral risk factor for chronic disease in Canada. Individual-level strategies are used in clinical medicine to target individuals for preventive intervention based on one or more risk factors. In contrast, this study examines the impact of a population-level intervention: a municipal policy outside the healthcare sector that influences the built and social environment. Research question What is the preventive effect of a municipal transportation policy to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This study's findings showing diabetes reductions from increases in walking from active travel are comparable to those of other studies that have modeled the effects of increases in walking through transportation policy initiatives. A modeling study examining the effect of a municipal transportation policy to increase active transportation in Ottawa, Ontario found that 1620 incident cases of diabetes could be prevented in 10 years by increases in public transit use [14] Another modeling study examining the impacts of high walking and cycling transport scenarios in the UK urban environment found a reduction of 7.2% in the diabetes burden by 2030 [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study's findings showing diabetes reductions from increases in walking from active travel are comparable to those of other studies that have modeled the effects of increases in walking through transportation policy initiatives. A modeling study examining the effect of a municipal transportation policy to increase active transportation in Ottawa, Ontario found that 1620 incident cases of diabetes could be prevented in 10 years by increases in public transit use [14] Another modeling study examining the impacts of high walking and cycling transport scenarios in the UK urban environment found a reduction of 7.2% in the diabetes burden by 2030 [13].…”
Section: Discussionmentioning
confidence: 99%
“…The built environment has also been linked to diabetes risk, for example, people living in highly walkable neighbourhoods have a lower incidence of diabetes than their counterparts living in low walkability neighbourhoods [12]. Additionally, modeling studies examining the effects of active transportation policies that encourage walking have demonstrated health benefits in terms of reductions in diabetes incidence [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Urban planning that curbs the car culture and provides a full range of services and retail, including healthy fresh produce, social spaces and green spaces within walking distance of people’s residence, along with well-developed active transportation and public transit systems is essential to the avoidance of chronic diseases (as well as injuries) and the promotion of mental health, healthy child development and quality of life (OPPI 2016 ; Tam 2017 ; BCCDC 2018 ). Official community plans have been reviewed for active living-related components and the impact of municipal transportation master plans on chronic disease incidence has been estimated (Arnason et al 2019 ). Both public health and planning communities (private and not-for-profit, as well as municipal) have supported community planners, fostering improved health through walkable, cycleable, complete and compact community design (Tam 2017 ) and incorporating green space into community planning and investments (EcoHealth Ontario 2017 ).…”
Section: Public Health and Municipal Planning Togethermentioning
confidence: 99%
“…In a second example, Arnason et al (2019) modelled the effects of transportation policy aimed at increasing active transport on the risk of diabetes, where diabetes risk was estimated from and validated using the CCHS data set. This allowed the researchers to understand the public health impact of specified active transport targets in terms of the number of diabetes cases avoided amongst commuters, for which the greatest impact was seen for adults over 45 years of age.…”
Section: Canadian Data and The Built Environmentmentioning
confidence: 99%